2018
DOI: 10.4103/npmj.npmj_24_18
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy computed tomography: A reliable and established tool for In vivo differentiation of uric acid from nonuric acid renal Stones

Abstract: DECT using the 3 generation CT scanners is highly sensitive in the determination of urinary calculi composition which will be very helpful to the treating surgeon in selecting the optimal modality of treatment as UA stones are amenable to medical therapy while most of the non-UA stones require surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
3
7
1
1
Order By: Relevance
“…In the present study, the proportion of hydroxyapatite and oxalic acid stones together was 53% followed by uric acid (23%) and cysteine (15%), respectively. As far as differentiation between uric acid and non-uric acid stones is concerned, the present study is in concordance with the observations of Ilyas et al who found 85% of their sample to be non-uric acid and only 15% to be uric acid stones [9]. The reason for the difference in the chemical composition of stones in different studies could be attributable to the inclusion criteria used and the difference in dietary habits and ethnicity of the affected population.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, the proportion of hydroxyapatite and oxalic acid stones together was 53% followed by uric acid (23%) and cysteine (15%), respectively. As far as differentiation between uric acid and non-uric acid stones is concerned, the present study is in concordance with the observations of Ilyas et al who found 85% of their sample to be non-uric acid and only 15% to be uric acid stones [9]. The reason for the difference in the chemical composition of stones in different studies could be attributable to the inclusion criteria used and the difference in dietary habits and ethnicity of the affected population.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the present study, Erdogan et al in their study found oxalic acid (42.9%) and hydroxyapatite (36.5%) as the dominant types on DECT while the in vitro analysis showed 22.9% as hydroxyapatite and 51.4% as oxalic acid calculi [15]. In another study, Ilyas et al found oxalic acid as the dominant type seen in 78.4% of their cases [9]. Manglaviti et al in their study did not diagnose hydroxyapatite in any of the cases and reported a dominance of oxalic acid (67.3%) calculi [16].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…несмотря на прогресс в диагностике МкБ, обусловленный использованием различных видов компьютерной томографии, появлением современных эндоскопических, малоинвазивных методов лечения без применения вторичной профилактики, риск рецидива камнеобразования составляет 50% в период от 5 до 10 лет с первых признаков проявления заболевания [12][13][14]. следует признать, что МкБ является мультидисциплинарной проблемой, решением которой занимается широкий круг специалистов: урологи, нефрологи, педиатры, детские урологи и нефрологи, семейные врачи, врачи ультразвуковой и лучевой диагностики.…”
unclassified